Unsteady Laminar Free Convection from a Vertical Cone with Uniform Surface Heat Flux - Pullepu, Bapuji; Ekambavanan, K.; Chamkha, A. J. J. (Nonlinear Analysis: Modelling and Control, 2008)
Numerical solutions of, unsteady laminar free convection from an incompressible viscous fluid past a vertical cone with uniform surface heat flux is presented in this paper. The dimensionless governing equations of the flow that are unsteady, coupled and non-linear partial differential equations are solved by an efficient, accurate and unconditionally stable finite difference scheme of Crank-Nicolson type. The velocity and temperature fields have been studied for various parameters Prandtl number and semi vertical angle. The local as well as average skin-friction and Nusselt number are also presented and analyzed graphically. The present results are compared with available results in literature and are found to be in good agreement.